Individualized rescuer change by a team leader during uninterrupted cardiopulmonary resuscitation: comparison with rescuer change in 2-min intervals. (August 2016) - Shin, Dong Hyuk; Cho, Jun Hwi; Park, Sang O
Abstract : Objective: Currently recommended cardiopulmonary resuscitation (CPR) guidelines to change rescuers in 2-min intervals do not consider the differences in the physical capability of individual rescuers. We compared the quality of chest compressions between the conventional rescuer rotation method (RC2, rescuers changed in 2-min intervals) and the novel rescuer rotation method (RCL, rescuers changed by a team leader's decision on the basis of gross assessment of the quality of chest compression). Methods: Ninety-six rescuers (48 pairs) were recruited and the sequence of the two-rescuer change methods (RC2 and RCL) was randomized. Forty-eight teams performed 8 min of uninterrupted two-rescuer CPR on a manikin with Skill-Reporter during two consecutive days (one method for each day). Results: The RCL method achieved deeper compression depth (mm) (52.6±3.8 vs. 49.5±4.7, P =0.002) and a higher number of correct chest compressions per minute (96.3±41.2 vs. 77.6±52.7, P <0.0001) than the RC2 method. However, the RCL method showed a longer total interruption time (s) than the RC2 method (21.1±3.9 vs. 14.8±1.0, P <0.0001) during 8 min of uninterrupted CPR. Conclusion: The quality of chest compression was better with RCL than the conventional RC2 method in terms of compression depth and proportions of correct compressions. RCL may be a practical alternative rescuer change strategy during uninterrupted chest compressions, especially when objective parameters to monitor the quality of chest compression are not readily available.